Trifurcation of the left common carotid artery: A case report - (:unkn) unknown (WILEY-LISS, 2001)
During dissection of the carotid triangle a carotid trifirucation was encountered. The left common carotid artery gave off three terminal branches: external carotid, internal carotid, and occipital arteries. The level of trifurcation was 35 mm above the superior margin of the thyroid, cartilage. Further, the superior thyroid artery arose from the common carotid artery instead of the external carotid. Herein, we describe the detailed anatomical features of the variant branching pattern of the left common carotid artery and its clinical implications. Clin. Anat. 14:58-61,2001. (C) 2001 Wiley-Liss,Inc.
Keywords: occipital artery; ascending pharyngeal artery; superior thyroid artery; variations; BYPASS; ISCHEMIA